(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Internet addiction has been associated with increased engagement in aggressive behavior, although the individual characteristics that may elevate the risk for these problematic behaviors are unknown. The present study was undertaken keeping these conditions in mind. Hence, the internet addiction and aggression their relations in adolescences were systematically measured and compared. Additionally the relationships of internet addiction and aggression and combining were also studied. For this, purpose 150 internet addicted and 150 non-addicted adolescences of Delhi were availability selected and they were administered Young’s Internet Addition Test and Aggression scale . The t- Test and Pearson’s product moment were applied to analyze the data. The results as follows: A significant difference between mean aggression scores of internet addicted and non-internet addicted adolescences and significant difference between mean aggression scores of male and female adolescences was obtained. A significant difference between mean internet addiction scores male and female adolescences was obtained. Significant positive relationship between internet addiction and aggression of adolescences was obtained. The study aims in making the adolescences aware of the various The review concludes with a summary of major research findings, as well as a consideration of future directions and implications for practice and policy.